Pengembangan Sistem Informasi Kredit Prestasi Berbasis Web (Studi Kasus: Fakultas Ekonomi dan Bisnis Universitas Brawijaya) - Aditya Yusril Fikri; Achmad Arwan; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The Faculty of Economics and Business Universitas Brawijaya (FEB UB) is one of the several faculties in Universitas Brawijaya. Every extracurricular and non-curricular activities at FEB UB need to be given awarding credit unit points (SKP) as motivation for students to improve their soft skills. To get SKP points, students must follow the activities of student institutions. There are problems that occur in the activities of student institutions namely the process of proposing proposals and LPJ activities. Students must come face to face with student staff to request the approval process. So students are constrained in the process of submitting activities. Student staff had difficulty in recording the process of submitting activities because the data was scattered in several files and made it difficult for student staff to recapitulate activities. Therefore a research on the development of an achievement credit system was conducted to overcome these problems. Development of a credit system for achievement applying the waterfall model method. the stages of system development starting from the study of literature, requirements engineering, design, system implementation to testing. Based on research conducted elicitation results obtained in the form of 9 types of actors, 55 functional needs and 1 non-functional needs. For the design produces architectural design, components, databases and interfaces, then carried out implementation. The achievement credit system is then carried out by white box testing in unit testing and integration while for black box testing in validation testing with 100% worth of test results. In addition, compatibility testing is performed on Firefox, Chrome, Opera, Edge, Internet Explorer, and Safari browsers.